The Role of Supervision and Nurses’ Job Satisfaction in Implementing Patient Safety Goals - Selvia Rahayu; Dedi Kurnia (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
The implementation of patient safety goals is essential to ensure safe nursing care and to prevent patient safety incidents. This study aimed to examine the relationship between nurses’ perceptions of supervision and job satisfaction and the implementation of patient safety goals at Hospital X in Bandung. A correlational analytic study with a cross-sectional design was conducted. Total sampling was applied, involving 89 staff nurses from all eligible units. Data were collected using a questionnaire distributed via Google Forms and analyzed using frequency distribution for univariate analysis and Kendall’s tau test for bivariate analysis. The results showed that 44.9% of respondents perceived supervision as good, 79.8% reported moderate job satisfaction, and 61.8% demonstrated good implementation of patient safety goals. There was a significant, moderately strong, and positive relationship between supervision and the implementation of patient safety goals (p=0.001; r=0.385). In contrast, job satisfaction showed a significant but weak negative relationship with the implementation of patient safety goals (p=0.037; r=−0.218). These findings indicate that supervision and nurses’ job satisfaction are associated with the implementation of patient safety goals. Therefore, hospital management should conduct regular evaluations of supervision, job satisfaction, and patient safety goal implementation and strengthen continuous engagement through safety talks or safety briefings.